Reports from the frontline: health workers describe COVID-19 risks and fears in five cities in Brazil - Carl Kendall; Ana Ecilda Lima Ellery; Nivaldo Carneiro Junior; Rosane da Silva Santana; Luciane Nascimento Cruz; Mírian Cohen; Marto Leal; Luana Nepomuceno Gondim Costa Lima; Maria Amélia de Sousa Mascena Veras; Maria de Fátima Pessoa Militão de Albuquerque; Karla Valéria Batista Lima; Celina Maria Turchi Martelli; et al. (BMC, 2023)
Abstract Background Health providers are under unprecedented pressures to perform in the COVID-19 health crisis and under unprecedented risks. We initiated a large mixed-method survey of health professionals in five large metropolitan areas in Brazil to document the risks and needs of health professionals. To initiate the study, we conducted formative research. Methods We conducted 77 open-ended semi-structured interviews online in a convenience sample of physicians, nurses, nurse technicians, and physiotherapists in Belem, Fortaleza, Porto Alegre, Recife, and São Paulo, Brazil. Design, data collection, and analysis were informed by Rapid Ethnographic Analysis (REA). Results Responses are organized into three themes that emerged in the interviews: the lack of preparation - both locally and nationally-for the pandemic and its effects on staffing and training; the overlap of personal, family, and professional risk and consequences; and inadequately addressed anxiety and suffering among health staff. Conclusions Our respondents were unprepared for the epidemic, especially the institutional sequelae and psychological cost. These consequences were exacerbated by both lack of leadership and sweeping changes undercutting the Brazilian health system noted by almost all participants.